Problem without initial conditions for a countable semilinear hyperbolic system of first-order equations - Kirilich, V. M.; Firman, T. I. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We derive sufficient conditions for the solvability of the problem without initial conditions for a countable semilinearhyperbolic system of first-order equations and establish conditions for the classical solvability of the initial-boundary valueproblem for countable hyperbolic systems of semilinear equations of the first-order in a semistrip.